2019
DOI: 10.33889/ijmems.2019.4.2-039
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Artificial Grasshopper Optimization (HAGOA) Meta-Heuristic Approach: A Hybrid Optimizer For Discover the Global Optimum in Given Search Space

Abstract: Meta-heuristic algorithms are used to get optimal solutions in different engineering branches. Here four types of meta-heuristics algorithms are used such as evolutionary algorithms, swarm-based algorithms, physics based algorithms and human based algorithms respectively. Swarm based meta-heuristic algorithms are given more effective result in optimization problem issues and these are generated global optimal solution. Existing swarm intelligence techniques are suffered with poor exploitation and exploration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…It is found that this mechanism has presented better search capabilities in several optimization issues. The standard ABC algorithm is shown in Figure 3 (Karaboga and Basturk, 2007; Dahiya et al , 2019).…”
Section: Proposed Workmentioning
confidence: 99%
“…It is found that this mechanism has presented better search capabilities in several optimization issues. The standard ABC algorithm is shown in Figure 3 (Karaboga and Basturk, 2007; Dahiya et al , 2019).…”
Section: Proposed Workmentioning
confidence: 99%
“…Umamaheswari et al (2018) utilized the Ant Lion Optimizer (ALO) to achieve the best possible maintenance schedules in context of preventive maintenance scheduling (PMS). Dahiya et al (2019) presented a meta-heuristic method to improve exploration and exploitation inside a search space known as hybrid artificial grasshopper optimization (HAGOA). Wei and Liu (2023) discussed optimising reliability for parallel and series systems when random shocks and constituents come from different discrete subpopulations within a heterogeneous population.…”
Section: Metaheuristic Approachesmentioning
confidence: 99%
“…Several robust metaheuristics were evolved in recent decades. Some were impressively effective in solving the OPF issue are hybrid firefly-bat algorithm [10], moth swarm algorithm HAGOA [11], whale optimization algorithm [12], adaptive group search optimization [13], ant lion optimizer [14], differential evolution algorithm [15], modified bacteria foraging algorithm [16], backtracking search algorithm [17], particle swarm optimization [18]. The multi-objective grey wolf algorithm [19,20] is used to optimize power flow, voltage stability, line losses, and carbon emissions [21].…”
Section: Introductionmentioning
confidence: 99%